Arbuscular mycorrhizal fungi in the East African Highland banana cropping systems as related to edapho-climatic conditions and management practices : case study of Rwanda - Gaidashova, S.V.; Asten, Piet J.A. van; Jefwa, J.M.; Delvaux, B.; Declerck, S. (Elsevier, 2010)
Root colonization, soil population density and diversity of arbuscular mycorrhizal (AM) fungi were assessed in 188 banana fields in contrasting soil types across five eco-regions in Rwanda (Butare–Gitarama, Gashonga, Bugarama, Kibungo, Ruhengeri). Root colonization was observed in all banana plants, whatever the soil type, field site and farm. The population density was higher on the wetter (1 300–1 500 mm yr?1) volcanic soils (Gashonga 59.8 and Ruhengeri 48.5 propagules 100 g?1 soil, respectively) as compared to the dryer (900–1?200 mm yr?1) soils derived from schist and granite (Butare–Gitarama 2.0, Kibungo 8.5, Bugarama 14.7 propagules 100 g?1 soil). The diversity was highest in Kibungo and lowest in Butare–Gitarama (10 and 2 spore morphotypes, respectively). These results suggested that AM fungi were widespread in banana cropping systems in Rwanda, but that root colonization, population density and diversity varied considerably depending on edapho-climatic conditions (i.e. rainfall, soil texture and P content) and soil management practices (tillage).